Solution phase synthesis and characterization of peptidyl chemosensors for Pb (ll) and As (lll) detection - Abdull Manap, Mohd Rashidi (2012)
A new fluorescent dipeptide Oansyl-Ala-Val-OMe (5) has been synthesized and characterized. Peptide 5 was synthesized based on sulfonation reaction between dipeptide and 5-(dimethylamino)naphthalene-1-sulfonyl chloride (Ons-CI) with molecular weight of m/z 435.2. Peptide 5 was obtained as a greenish solid in 80% yield. This compound was in a form of diastereomer in a 1:5 mixture ratio and it was not separated. Peptide 5 was characterized by melting point, IR, NMR, UPLC, GC-MS and HR-MS. Meanwhile another fluorescent dipeptide, Oansyl-Ala-GIY-OH (6) was purchased. The fluorescence intensity of peptide 5 was measured at pH 5 with excitation and emission wavelengths of 289 nm and 487 nm, respectively where as the excitation and emission wavelengths of peptide 6 at pH 12 were 331 nm and 524 nm, respectively. Fluoresence difference measurement was used for measurement. Effect of amount of reagent, different pH, dynamic range, reproducibility, interference and validation were studied. 4.0 IJM of peptide 5 in a mixture of methanol water (4: 1) was observed to be the optimum concentration for detection of Pb(II). Meanwhile 1.5 IJM of peptide 6 in 100% aqueous solution was needed for optimum detection of As(III). The working medium of peptide 5 is at pH 5, meanwhile peptide 6 at pH 12. Limit of detection (LOD) for detection of Pb(lI) and As(lIl) were calculated to be O.OS jJM and 1.S6 jJM respectively. The RSD of the reproducibility were 2.03% and 9.66% for 4.00 jJM Pb(lI) and 7.S4 jJM As(III). The presence of foreign ions at 1:1 molar ratio of interfering ion: studied metals did not affect the determination of Pb(lI) and As(lIl) based on the low percentage of interference. The developed detection systems were validated with the established method of inductively coupled plasma optical emission spectrometry (ICP-OES).